IN THE PRIMARY SCHOOL SYSTEM AND TECHNOLOGIES OF DISTANCE LEARNING BASIC PRINCIPLES OF SCIENCE IN MATHEMATICS (Academia Science Repository, 2023)
In this article, readers in the learning process for the formation of skills and knowledge about technologies from the use of a distance learning system principles and lit.